Hospital At Home: Sustainable Healthcare in Developing Countries through Reducing Average Length of Stay in Hospitals - Nerminathan, Veerasingam; Adlan, Wan Noor Amalyna Binti Wan Fadzil; Nerminathan, Arany A (International Journal of Management and Sustainability, 2014)
Increasing health costs is becoming a burden for countries all over the world, and for the developing countries, it may reach a point where the government may not be able to provide the healthcare demanded by the public. It is not solely based on increasing the health spending; every aspect of health expenditure should be considered to improve efficiency. One of the aims of the tenth Malaysian plan is improving efficiency and reducing waste. We propose a measure to improve efficiency by decreasing the average length of stay, given the fact that hospital care is far more expensive than care in the community. Planned and managed early discharge to the homes, supported by community nurses and doctors, in addition to improved communications, can reduce average length of stay. At present the length of stay is 3.52 days in the public sector and 2.71 days in the private sector. There is a significant variation between states, not only for the average length of stay, but also for the bed turnover interval; providing less of an incentive for earlier discharge. By reducing the length of stay by merely 0.5 days, we suggest there would be savings up to RM250 million savings each year, and with other additional measures, there would be significant savings, making healthcare more affordable and sustainable, making Malaysia a shining example among developing countries.